PENDAMPINGAN PENGURUSAN IZIN USAHA PRODUK â€œNOGAâ€ PADA KELOMPOK TANI MUKTI DESA SUKAJADI KABUPATEN BOGOR - Setyawan, Iwan; Laksono, Rudi; Gultom, Junias Robert (Jurnal Abdi Insani, 2022)
Noga is a type of traditional snack produced by members of the Mukti Farmer Group in Sukajadi Village, Bogor Regency. This Noga product has become an icon of the village and has the potential to expand its target market, but is constrained by the absence of business legality. Partners do not really understand the importance and benefits of having a business license. In addition, partners also do not understand the process of managing the business license and the technology layman when they have to register through the OSS system. The purpose of this service activity is to provide an understanding of the benefits of having a business license for partner businesses, mapping the position and classification group of partner businesses and to obtain a Nomor Induk Berusaha (NIB). The method of activity used, first is the socialization method used to educate partners about the importance and benefits of having a business license. Both methods of self-assessment to assess the position and classification group of partner businesses. Finally, the mentoring method to take care of the Nomor Induk Berusaha (NIB). As a result of this community service activity, partners are able to understand and be aware the importance and benefits of having a business license for the development and sustainability of their business in the future. Based on this awareness, partners have a strong desire to obtain a business license and partners are willing to be given assistance in the process of managing the business license. The results of the self-assessment place the partner's business position in the low-risk business category and are included in the micro and small business classification group so that the business license that must be owned is NIB. The results of the assistance in managing business permits, partners currently have an NIB.